PERBEDAAN KADAR TOTAL KOLESTEROL TERHADAP PEMAKAIAN OBAT HALOPERIDOL DAN RISPERIDON PADA PASIEN SKIZOFRENIA DI RSUD PROF. DR. M. ILDREM - ILHAM SYAHPUTRA; NANDA SARI NURALITA (JURNAL ILMIAH KOHESI, 2022)
Schizophrenia is one of the most common psychotic disorders in the world. Schizophrenia treatment uses antipsychotics torelieve symptoms experienced by patients. Giving antipsychotics can cause bad side effects in schizophrenics. Side effectsobtained from the use of antipsychotics consist of extrapyramidal extracts, metabolic syndrome and also weight gain whichworsens the patient's condition. To find out the difference in total cholesterol levels on the use of the dhaloperidol andrisperidone in schizophrenic patients at Psychiatric Hospital Prof. Dr. M. Ildrem. which took from August to December 2019.Numerical analytic by using cross sectional design. Data on total cholesterol levels taken through peripheral blood wereobtained from 40 samples and then analyzed using the Mann Whitney test. Mann Whitney test results showed that there wasa significant difference between the use of haloperidol and risperidone in schizophrenic patients with a P value = 0.001(p <0.05). Risperidone drug using is higher risk compared with haloperidol drugs. The use of risperidone has a significantdifference with haloperidol on total cholesterol levels in schizophrenic patients.